Biblical Codes in the Ancient Ukrainian and Lithuanian Literary Connections - Микитівна Левченко, Наталія (Slavistica Vilnensis, 2009)
Since ancient times the cooperation between Ukrainian and Lithuanian cultures has spread into different areas of their respective lives. As a result of the historical dissemination of Christianity across Europe, the Bible has become a point of reference for the literary traditions of these two peoples. The theory of Bible interpretation is revealing at four semantic levels: literal, allegoric, moral and anagogic. The author argues that the writers of both ancient Ukraine and Lithuania employed the foursemantic levels of biblical hermeneutics in the poetics of their literary texts.